Parental Punishment and Adolescents’ Loneliness: A Moderated Mediation Model of General Self-Concept and Teacher–Student Relationships - Luo, Yun; Wu, Anyi; Zhang, Hui (Frontiers in Psychology, 2021)
Background:The literature clearly shows that loneliness adversely affects physical and mental health. It is therefore necessary to explore the related influencing factors and mechanisms. This study investigated the mediating role of general self-concept in the association between parental punishment and adolescent loneliness and the moderating role of the teacher-student relationships in Chinese students. Methods:The date obtained from 1,169 Chinese junior and senior high school students age range from 10 to 18, using the self-report questionnaires including the Egna Minnen av Barndoms Uppfostran (EMBU), Self-Description Questionnaire (SDQ), Student-Teacher Relationship Scale (STRS), and UCLA Loneliness Scale. This study implemented a network of questionnaires that respondents completed in the same sitting. The IBM SPSS 22.0 software was used to analyze resulting data, while the PROCESS macro program was used to analyze the moderated mediating effect. Results: (1) Parental punishment had a positive predictive effect on adolescent loneliness; (2) Parental punishment could not only predict adolescent loneliness directly, but also indirectly through the mediating effect of general self-concept, and (3) The teacher-student relationships moderated the influence of parental punishment on general self-concept. Conclusions: Adolescent loneliness is less affected by parental punishment when the teacher-student relationships are better. On the other hand, when adolescents are punished less by their parents and have good teacher-student relationships, they have a higher general self-concept. Limitations: This study adopted a cross-sectional research design to investigate the factors influencing adolescent loneliness, but was therefore unable to draw causal inferences.